Shot Peening Effect on Reduced Graphene Oxide-based AA1070 Alloys Produced by Stir Casting Technique - İremnur Bülbül; Remzi Varol; Mehmet Fahri Saraç (Journal of Advanced Research in Natural and Applied Sciences)
The shot peening effects of reduced graphene oxide (rGO) additive on the structural, residual stress, hardness and surface roughness of AA1070 composites were investigated and reported in detail for the first time. It can be said that with increasing amounts of rGO added into AA1070 alloy, rGO is randomly distributed into the Al matrix with increasing amounts. The XRD analysis shows that there is no trace of carbon in the Al matrix, showing the the carbon structure did not diffuse into Al matrix during casting. However, in the EDS analysis, it was determined that the carbon value increased due to the increased presence of rGO. Although it has been studied according to the differences in ball diameters, it has been observed that the relative differences between the ball forging times affect the surface roughness changes in the samples. It was also observed that the hardness values were directly related to the ball forging times. On the other hand, the surface area of the forged matrix decreases in the presence of increasing rGO. While the hardness should increase after shot peening, cold deformation is not expected on the surface with the increase in the presence of rGO, and therefore, a decrease in the hardness value of the shot peened surface occurs. This is compatible with the residual stress results as well.